Passive vibration control of cylindrical offshore components using pipe-in-pipe (PIP) concept: An analytical study - Matin Nikoo, H.; Bi, Kaiming; Hao, H. (Elsevier, 2017)
© 2017 Elsevier Ltd This paper aims to propose a design of using the revised PIP system to control vortex induced vibrations (VIV) of cylindrical structural components. Analytical studies are carried out to examine the effectiveness of the proposed method. To this end, the fluid-induced vibration of a single pipe is investigated and the equation of motion of the system is solved and validated by the experimental data. This single pipe system is then extended to the proposed PIP system and its dynamic behaviour under the excitation of vortex shedding is simplified as a Two-Degree-of-Freedom (2DoF) system. The optimal damping ratio and tuning frequency of the revised PIP system are obtained through a series of numerical searching technique and sensitivity analyses. Explicit formulae are also derived for practical ease of use. The governing equation of the system under VIV is solved in the time domain using the MATLAB/Simulink program. The responses of the single pipe system and the proposed PIP system due to vortex shedding are calculated and compared. Analytical results demonstrate that the proposed PIP system can significantly suppress the VIV of offshore cylindrical components. It could be then a cost-effective passive solution to suppress vibration of offshore cylindrical components.